Starling‐Like Flow Control of a Left Ventricular Assist Device: In Vitro Validation. Issue 3 (23rd December 2013) - Gaddum, Nicholas R.; Stevens, Michael; Lim, Einly; Fraser, John; Lovell, Nigel; Mason, David; Timms, Daniel; Salamonsen, Robert
<x xml:space="preserve">Abstract</x> Abstract The application of rotary left ventricular (LV) assist devices (LVADs) is expanding from bridge to transplant, to destination and bridge to recovery therapy. Conventional constant speed LVAD controllers do not regulate flow according to preload, and can cause over/underpumping, leading to harmful ventricular suction or pulmonary edema, respectively. We implemented a novel adaptive controller which maintains a linear relationship between mean flow and flow pulsatility to imitate native Starling‐like flow regulation which requires only the measurement of VAD flow. In vitro controller evaluation was conducted and the flow sensitivity was compared during simulations of postural change, pulmonary hypertension, and the transition from sleep to wake. The Starling‐like controller's flow sensitivity to preload was measured as 0.39 L/min/mm Hg, 10 times greater than constant speed control (0.04 L/min/mm Hg). Constant speed control induced LV suction after sudden simulated pulmonary hypertension, whereas Starling‐like control reduced mean flow from 4.14 to 3.58 L/min, maintaining safe support. From simulated sleep to wake, Starling‐like control increased flow 2.93 to 4.11 L/min as a response to the increased residual LV pulsatility. The proposed controller has the potential to better match device outflow to patient demand in comparison with conventional constant speed control.